2019
DOI: 10.1002/ijc.32615
|View full text |Cite|
|
Sign up to set email alerts
|

The NEDD4‐1 E3 ubiquitin ligase: A potential molecular target for bortezomib sensitivity in multiple myeloma

Abstract: E3 ubiquitin ligases primarily determine the substrate specificity of the ubiquitin‐proteasome system and play an essential role in the resistance to bortezomib in multiple myeloma (MM). Neural precursor cell‐expressed developmentally downregulated gene 4‐1 (NEDD4‐1, also known as NEDD4) is a founding member of the NEDD4 family of E3 ligases and is involved in the proliferation, migration, invasion and drug sensitivity of cancer cells. In the present study, we investigated the role of NEDD4‐1 in MM cells and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 56 publications
(126 reference statements)
0
22
0
Order By: Relevance
“…In this study, we further proceeded to clarify the regulatory mechanism of miR-27 through targeting the NEDD4/Notch1 axis in MM cells. It is noted that E3 ubiquitin ligase NEDD4 downregulation has been associated with unfavorable prognosis of MM patients, due to the contribution to drug resistance ( 22 ). Emerging studies documented that NEDD4 exerted a promotive regulation of autophagy through different mechanisms in different types of cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we further proceeded to clarify the regulatory mechanism of miR-27 through targeting the NEDD4/Notch1 axis in MM cells. It is noted that E3 ubiquitin ligase NEDD4 downregulation has been associated with unfavorable prognosis of MM patients, due to the contribution to drug resistance ( 22 ). Emerging studies documented that NEDD4 exerted a promotive regulation of autophagy through different mechanisms in different types of cells.…”
Section: Discussionmentioning
confidence: 99%
“…A wide array of studies have revealed cytogenetic and epigenetic changes in MM cells, which influence cellular proliferation, apoptosis, autophagy, and metastasis through different mechanisms, including the regulatory effects of microRNAs (miRNAs) on the progression of MM (5). miRNAs are small single-stranded RNAs (19)(20)(21)(22) nucleotide in length), which participate in various malignant biological processes of MM (6). Different effects have been identified for specific miRNAs on MM cells, including pro-tumoral and antitumoral properties.…”
Section: Introductionmentioning
confidence: 99%
“…Our observation suggests that reduced GSK3 activity as a result of insulin signaling may decrease NEDD4 levels and thus put a brake on insulin and growth factor signalling through a negative feedback loop. However, in human cells NEDD4 can directly bind to and ubiquitinate AKT which is prior phosphorylated on pS473, to degrade active AKT 52 . Thus, decreased GSK3 activity and therefore reduced NEDD4 levels would increase active AKT pS473, providing a positive feedback for insulin and growth factor signalling and glucose uptake to counteract the negative feedback and establish a steady state.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, NEDD4 is highly expressed in erlotinib-resistant NSCLC cells and cisplatinresistant nasopharyngeal carcinoma cells [41] . Nonetheless, upregulation of NEDD4 resensitized multiple myeloma cells to bortezomib treatment via ubiquitination of Akt and degradation of pAkt-Ser473, while downregulation of NEDD4 resulted in bortezomib resistance in multiple myeloma cells [42] . What's more, Akkaya et al [43] also demonstrated NEDD4 as a ubiquitin ligase for ATP binding cassette subfamily B member 1, which is a multidrug resistance pump that mediates drug resistance, indicating that NEDD4 directly participates in drug resistance.…”
Section: Nedd4 Familymentioning
confidence: 99%